The three billy goats: favourite tales (big book) - Russel, Chris (Ladybird London, 1998)
"The Three Billy Goats Gruff" is a classic fairy tale about three billy goats who want to cross a bridge to reach lush green pastures. However, a fearsome troll lives under the bridge and threatens to eat them. The smallest billy goat crosses first, and when the troll confronts him, the goat cleverly tells the troll to wait for his bigger brother, who would be more delicious. The troll lets him pass. Next, the middle-sized goat tries to cross, using the same tactic. Finally, the largest billy goat crosses the bridge, and when the troll tries to attack, the goat uses his strength to butt the troll off the bridge. In the end, all three billy goats enjoy the green grass, and the troll is never seen again. The story teaches lessons about bravery, cleverness, and teamwork.